ELISA: METHODS, PRINCIPLES AND APPLICATION (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Enzyme-linked immunosorbent assay (ELISA) is widely used as diagnostic tools in medicine and as quality control measures in various industries; they are also used as analytical tools in biomedical research for the detection and quantification of specific antigens or antibodies in a given sample. This article discusses the history, types, principle of the method, and importance of enzyme immunoassay in diagnostics.